How age-of-death and mode-of-death impact perceptions of the deceased. Issue 8 (14th September 2019) - Bolt, Emily Lena Wight; Corbin Dwyer, Sonya; Buckle, Jennifer L.; Zendel, Benjamin Rich
Abstract: The goal of the current study was to explore how age-of-death (AOD) and mode-of-death MOD simultaneously influence ratings of sympathy, empathy, and tragedy toward the deceased in order to assess social value. Three hundred and fifty-eight participants, mainly undergraduates, responded to a series of vignettes that described a MOD (suicide, accident, or stroke) counterbalanced with three AODs (younger, middle-aged, and older). Overall, ratings of sympathy, empathy, and tragedy declined as AOD increased; however, the effect of AOD was not consistent across all MODs. The pattern of results suggests that death norms and perceived control of death impact the perception of the deceased.